(untitled) (Bangladesh Journal of Botany, 2014)
Line × tester analysis involving seven early maturing lines and four high yielding testers, made to produce 28 F1s hybrids. The F1 data revealed that both additive and non-additive gene were important in controlling yield contribution in Indica rice. Variances were significant for GCA and SCA effects for all the characters indicating the significance of both additive and non-additive genes. There was high proportion of non-additive genes for the expression of different traits. Cultivars Anjali, MTU-7029 and BPT-5204 were identified as best general combiners for yield and yield traits among the parents. The most promising specific combiners for grain yield and its contributing traits were Govind × HUR 105, NDR 97 × HUR 4-3, Anjali × HUR 4-3, NDR 97 × MTU 7029, Vandana × BPT 5204, Shanthi × HUR 105, Anjali × MTU 7029 and Shanthi × BPT 5204. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18026 Bangladesh J. Bot. 42(2): 247-255, 2013 (December)